The relationship between social capital and entrepreneurship in Indonesia - Djatnika, Ariq Fazlurrahman; Handayani, Dwini (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Entrepreneurship encompasses a range of components, including passion, attitude, and behavior, which serve as manifestations of calculated risk-taking courage motivated by an individual's personal determination and capabilities. Individuals exhibiting such a disposition are frequently recognized as self-employed individuals or entrepreneurs. Entrepreneurs, by leveraging their ability to recognize commercial opportunities and mobilize resources, play a vital role in fostering economic growth and innovation. Methods: The method used in this study is binary logistic regression involving data from Indonesia Family Life Survey (IFLS) 2014 fifth wave. The study identified three dimentions of social capital that included trust, participation, and cooperativeness. Findings: This is particularly evident in developing economies, where entrepreneurship serves as a key driver of employment and industry expansion. For example, in Indonesia, where Micro, Small, and Medium Enterprises (MSMEs) and self-employed individuals account for a large portion of the economy, the entrepreneurial spirit fuels job creation, enhances productivity, and stimulates market competition. As of recent data, MSMEs contribute to more than 60% of Indonesia's Gross Domestic Product (GDP) and nearly 97% of its total employment. This study aims to analyze the relationship between social capital and entrepreneruship in Indonesia. Conclusion: The result showed that participation dimension of social capital significantly positively associated with entrepreneurship. The result also showed that trust dimension of social capital signicantly negatively associated with entrepreneruship. Additionally, all control variables, including age, gender, marital status, and economic conditions, showed statistically significant relationships with entrepreneurship. Older individuals, women, married individuals, and those with extroverted personalities are more likely to engage in entrepreneurship. Conversely, those living in urban areas and regions with higher gross domestic regional product (GDRP) are less inclined towards entrepreneurial activities, possibly due to alternative employment opportunities. Novelty/Originality of this article: These results underscore the complex role of social capital in entrepreneurship and highlight the importance of policy measures that foster social capital to support entrepreneurial activity in Indonesia.